Strategi Efektif Mengubah Generalisasi Menjadi Pemahaman Konkret Untuk Siswa Sekolah Dasar - Agustina, Utari; Adila, Nur; Syarifuddin, Syarifuddin (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This article discusses effective strategies for turning generalizations into concrete understanding among elementary school students. By using active learning methods, concrete manipulatives, and context-based approaches, this research aims to improve students' ability to understand abstract concepts. This research was conducted in several elementary schools involving 150 grade 4 and 5 students as subjects. The results showed a significant increase in understanding of math and science concepts after implementing this strategy.